2018
DOI: 10.1111/ejn.14181
|View full text |Cite
|
Sign up to set email alerts
|

Copper in the suprachiasmatic circadian clock: A possible link between multiple circadian oscillators

Abstract: The mammalian circadian clock in the suprachiasmatic nucleus (SCN) is very robust, able to coordinate our daily physiological and behavioral rhythms with exquisite accuracy. Simultaneously, the SCN clock is highly sensitive to environmental timing cues such as the solar cycle. This duality of resiliency and sensitivity may be sustained in part by a complex intertwining of three cellular oscillators: transcription/translation, metabolic/redox, and membrane excitability. We suggest here that one of the links con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 293 publications
(407 reference statements)
0
4
0
Order By: Relevance
“…Intriguingly, copper may play an important role in the regulation of circadian rhythms. The copper chaperone and transporter Atox1 (Lee et al, 2013) is expressed rhythmically in the SCN, as is ATP7A (Yamada & Prosser, 2020). Additionally, electrophysiological studies in acute SCN slices from mice demonstrated that modulation of copper availability can shift circadian clock phase.…”
Section: Copper and Circadian Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, copper may play an important role in the regulation of circadian rhythms. The copper chaperone and transporter Atox1 (Lee et al, 2013) is expressed rhythmically in the SCN, as is ATP7A (Yamada & Prosser, 2020). Additionally, electrophysiological studies in acute SCN slices from mice demonstrated that modulation of copper availability can shift circadian clock phase.…”
Section: Copper and Circadian Rhythmsmentioning
confidence: 99%
“…Unlike copper chelation however, these circadian phase shifts were independent of NMDAR activation (Yamada & Prosser, 2014). Yamada and Prosser (2020) suggest that these results may best be explained by biphasic effects of copper in the SCN where too little or too much copper can phase‐shift the SCN clock and activate or inhibit distinct signalling pathways.…”
Section: Copper and Circadian Rhythmsmentioning
confidence: 99%
“…This partly explains how intracellular Ca 2+ generates and maintains circadian rhythms in the mouse SCN and behavioral rhythms in flies [ 224 , 236 , 237 , 238 ]. As with Ca 2+ , Cu 2+ was also found to induce nighttime phase shifts of the SCN clock in a mitogen-activated protein kinase (MAPK)-dependent manner [ 239 ]. In line with this, Feeney et al showed that intracellular Mg 2+ exhibits robust cell-intrinsic circadian rhythms and acts as a cell-autonomous timekeeping factor to determine circadian rhythms of gene expression, ATP-dependent energy expenditure, and mTOR-mediated translation in both a human cell line and a unicellular alga [ 240 ].…”
Section: The Role Of Metabolic Cues In Circadian Rhythms and Disordersmentioning
confidence: 99%
“…Highlighting a new realm of investigation, there is evidence of a contribution of a novel factor in SCN timekeeping—namely copper (Yamada & Prosser, ). Both background literature and new experimental results raise the possibility that copper is involved in light mediated glutamatergic resetting of the SCN.…”
Section: Extra‐scn Oscillatorsmentioning
confidence: 99%